Pengaruh Disleksia terhadap Perkembangan Anak - Dhila Thasliyah; Anjely Doni Lasmi; Visakha Vidyadevi Wiguna (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The purpose of preparing this article is to understand more deeply about effect of dyslexia in children aged 1 to 5 years old. The method used is a literature study from various sources, such as: 1) journal reviews, 2). scientific writing articles. Selection of journals and articles focused on children with dyslexia, while reviews of articles and journals were carried out in the last 10 years from 2010-2021. Dyslexia is defined as a syndrome that has difficulty learning the components of words and sentences as well as difficulties in learning about everything related to time. The risk factors for dyslexia in children are genetic and family environment. The impact of dyslexia on children’s development can be in the form of difficulties in reading skills, personality, behavior, and quality of life disorders. In addition, it also affects language development disorders, declarative consolidation disorders during sleep, and dyslexia comorbidities.